College Preparation in a Low-Income, Urban, Public High School: A Case Study - Foote, Catherine Castillo (ProQuest Dissertations & Theses, 2011)
College Preparation in a Low-Income, Urban, Public High School: A Case Study College preparation for low-income, urban, minority students is the subject of this ethnographic case study. Previous research indicates that for these students the notion that college is the next step after high school graduation may be considered unrealistic, especially if parents or other family members lack postsecondary education experiences. This was a qualitative case study of one comprehensive urban high school located in a predominantly middle to upper class White neighborhood. People residing in this neighborhood were older and the majority no longer had children of high school age. Therefore, over half the student body (70%) were African-American teenagers bused from surrounding low-income, urban areas. The purpose of the study was to look for evidence of indicators believed necessary to create and foster a college-going culture in a low-income, urban, public high school. The findings suggested that students from lower socioeconomic groups, those with high aspirations, and even those who qualify for college acceptance, often lack the information and support necessary to negotiate the postsecondary application and enrollment processes. Adopting a college-going mission is as much a mentality as it is an objective, and requires active awareness and participation by all stakeholders including students, families, schools, and the community.